Peptide linker increased the stability of pneumococcal fusion protein vaccine candidate - Zane, Luciano; Kraschowetz, Stefanie; Trentini, Monalisa Martins; Alves, Vitor dos Santos; Araujo, Sergio Carneiro; Goulart, Cibelly; Leite, Luciana Cezar de Cerqueira; Gonçalves, Viviane Maimoni (Frontiers in Bioengineering and Biotechnology, 2023)
Streptococcus pneumoniae is a bacterial pathogen exclusive to humans, responsible for respiratory and systemic diseases. Pneumococcal protein vaccines have been proposed as serotype-independent alternatives to currently used conjugated polysaccharide vaccines, which have presented limitations regarding their coverage. Previously in our group, pneumococcal surface protein A (PspA) and detoxified pneumolysin (PdT) were genetically fused and the hybrid protein protected mice against pneumococcal challenge, offered higher cross-protection against different strains and showed greater opsonophagocytosis rate than co-administered proteins. As juxtaposed fusion was unstable to upscale production of the protein, flexible (PspA-FL-PdT) and rigid (PspA-RL-PdT) molecular linkers were inserted between the antigens to increase stability. This work aimed to produce recombinant fusion proteins, evaluate their stability after linker insertion, both in silico and experimentally, and enable the production of two antigens in a single process. The two constructs with linkers were cloned into Escherichia coli and hybrid proteins were purified using chromatography; purity was evaluated by SDS-PAGE and stability by Western blot and high performance size exclusion chromatography. PspA-FL-PdT showed higher stability at -20 °C and 4 °C, without additional preservatives. In silico analyses also showed differences regarding stability of the fusion proteins, with molecule without linker presenting disallowed amino acid positions in Ramachandran plot and PspA-FL-PdT showing the best scores, in agreement with experimental results. Mice were immunized with three doses and different amounts of each protein. Both fusion proteins protected all groups of mice against intranasal lethal challenge. The results show the importance of hybrid protein structure on the stability of the products, which is essential for a successful bioprocess development.